2011
DOI: 10.1016/j.bbr.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of extracellular signal-regulated kinase (ERK) activity with SL327 does not prevent acquisition, expression, and extinction of ethanol-seeking behavior in mice

Abstract: Although extracellular signal-regulated kinase (ERK) activity is essential for the acquisition of a variety of associative learning tasks, its involvement in the acquisition and extinction of ethanol (EtOH)-induced conditioned place preference (CPP) remains unknown. Therefore, in these experiments we examined the effects of the ERK-kinase (MEK)-inhibitor SL327 on acquisition and expression of EtOH-CPP as well as the dose-and time-dependent effects of SL327 on CPP extinction. The parametric findings of Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
3
21
2
Order By: Relevance
“…In the CPP model, the alcohol metabolite ACD-CPP is dependent on D1-R activation and the development of ACD-CPP can be attenuated by the MEK inhibitor, PD98059 253 . In contrast, a previous study has indicated that the systemic SL327 administration in the ERK-independent learning mechanism in EtOH-CPP did not affect the acquisition, expression and extinction of EtOH-CPP (2g/kg) as well as pERK after acute EtOH administration (2.5g/kg) 254 . However, EtOH-CPP has been shown to be established by the lower dose of EtOH (1g/kg) in D1-R dependent manner 253 , which is sufficient to induce pERK induction as described above.…”
Section: Erk Signaling and Drug Addictioncontrasting
confidence: 69%
“…In the CPP model, the alcohol metabolite ACD-CPP is dependent on D1-R activation and the development of ACD-CPP can be attenuated by the MEK inhibitor, PD98059 253 . In contrast, a previous study has indicated that the systemic SL327 administration in the ERK-independent learning mechanism in EtOH-CPP did not affect the acquisition, expression and extinction of EtOH-CPP (2g/kg) as well as pERK after acute EtOH administration (2.5g/kg) 254 . However, EtOH-CPP has been shown to be established by the lower dose of EtOH (1g/kg) in D1-R dependent manner 253 , which is sufficient to induce pERK induction as described above.…”
Section: Erk Signaling and Drug Addictioncontrasting
confidence: 69%
“…Extinction consisted of AM and PM sessions during which animals received four, 30-min non-reinforced exposures to each of the CS+ and CS- cues separately as previously described ( see Groblewski et al, 2011). Specifically, for the AM session, animals were weighed, injected with saline, and immediately placed on the CS- cue for 30 mins.…”
Section: Methodsmentioning
confidence: 99%
“…Extinction was defined a priori as a significant reduction in place preference that was determined by Bonferroni-adjusted within-subject comparisons of preferences on Test 1 and 2 (paired t-tests) for each group following an initial two-way ANOVA (Group x Test) (Groblewski et al, 2011). Additional between-group analyses of the time spent on the Grid floor were performed including the Conditioning Subgroup (G+ and G−) as a third factor (Cunningham et al, 2003) and these data are reported in Table 1 for both experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic morphine and spontaneous withdrawal (24 h) is not associated with alterations in the content of phosphorylated MEK1/2 in the brain [1]. EtOH-related learning and EtOH reward in mice are not impaired by the systemically administered MEK-inhibitor SL327 [7]. However, central amygdala ERK signaling pathway is critical to incubation of cocaine or opiate craving [10,13].…”
Section: Introductionmentioning
confidence: 95%